Medical and dental effects of energy drinks consumption. Literature review. (International Journal of Medical and Surgical Sciences, 2017)
The energy drinks have undergone exponential hikes over the last years worldwide, in adults, youth, and even children. Among its components can be found: caffeine, guarana, taurine, ging-Seng, L-carnitine, creatinine or glucuronolactone, citric acid and phosphoric acid, among others. A responsible and occasional consumption should not pose major problems, but this is not the case. The medical effects are usually caused by their abuse, like: headaches, palpitations, insomnia, sweating, abdominal pain, vomiting, nausea, gastroesophageal reflux, facial numbness, bloating, tremor, diarrhea and even addiction, among others. While in the dental level, specifically on the dental enamel, the most severe impact is the erosion and the lesser impact is tooth staining, which has not yet been fully investigated, also have been described the development of hypersensitivity. A timely prevention and diagnosis are essential to minimize the damage caused by prolonged use of these products. It is essential to avoid a possible trend or “fad” associated with mixing energy drinks and alcohol and even drugs, of which they are not fully known the possible risks that could potentially cause. Due to its exponential growth it is essential to have an updated knowledge about the consumption of these beverages. The high consumption of energy drinks maintained over time is associated with negative effects at the medical and dental level. Further research is necessary to prevent, treat and rehabilitate the consequences produced by the consumption of these products.